(untitled) (Itinera, 2015)
Basing on the characterization of exáiphnes in Parm., 156 c 8-157 b 3, as well as of the relationship between téchne and nómos in Polit. 294 a 6-299 e, an integration of Plato’s philosophy into the contemporary discourse concerning improvisation is attempted. Special attention is given also to the description of Socrates’ midwifery (Theaet., 149 a 1-151 d 3), since by means of Plato’s description Socrates’ activity can be perceived as quintessence of a practice which, like improvisation, without any predetermination, while concretely proceeding invents the norm consonant with each singular situation of ist proceeding.